Reasons for extraction of permanent teeth - An institutional study - KEERTHANA, R.; KUMAR, M.P.SANTHOSH; CHAUDHARY, MANJARI (The journal of contemporary issues in business and government, 2021)
Cause for tooth extraction had large geographical and cultural differences in different Countries. A decrease in the number of teeth can serve as an indicator of socio-economic and oral hygiene level. A reduction in the number of teeth may result in poor dietary habits and deterioration of quality of life. The aim of this study was to investigate the primary reasons for extraction of permanent teeth and to evaluate its association with age, gender among patients treated in Saveetha Dental College and hospital. In this retrospective cross-sectional study, digital case records of all patients reported to saveetha dental college and hospital from June 2019 to March 2020 were reviewed. All adult patients who underwent extraction of teeth were included in the study. Demographic details of patients and the reasons for extraction of the permanent tooth were recorded from digital case records, clinical photographs and radiographs. Retrieved data was analysed using IBM SPSS Software Version 23.0. Descriptive statistics and tests of association for categorical variables by Chi square tests were done and results were obtained. P value < 0.05 was considered statistically significant. The common reason for the extraction of permanent teeth was dental caries (34.2%). Tooth extraction was more in the age group 18-35 years (41.2%) and the most common reason was dental caries (41.7%). The association between age and reasons for tooth extraction was statistically significant.(p<0.001).Tooth extraction was more in the males (58.6%) compared to females (41.3%) and the most common reason for extraction in the males was dental caries (31.3%) and in females was dental caries (38.2%). The association between gender and reasons of tooth extraction was statistically significant(p<0.001). The association between age and gender of the patients undergoing extraction of permanent teeth was also statistically significant.(p<0.001). Within the limits of the study, dental caries was the most common reason for the extraction of permanent teeth. Males underwent more extractions than females and the predominant age group undergoing extraction of teeth were 18-35 years. This fact should be kept in mind while planning preventive programs and more emphasis should be given for prevention of dental caries or periodontal disease based on age of the target population.